1998
DOI: 10.1255/jnirs.137
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of Soils by the near Infrared Technique

Abstract: There are physical, physico-chemical and chemical parameters which can be used as a basis for the characterisations of soils. Some of these characterisation methods are slow, laborious and show very empiric character. Near infrared (NIR) reflectance spectroscopic methods were used for substitution of conventional soil analysis procedures. Seven different soil characteristics (humus, calcium carbonate, total nitrogen, dead water content, yarn test by Arany, mechanical composition, hygroscopic water content) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2007
2007
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…However, data from Coûteaux et al (2003) for a fairly homogeneous set indicated that prediction accuracy was greater for Ct than for Nt (validation R 2 and CV were 0.99 vs. 0.98 and 6% vs. 10%, respectively). Similarly, data from Salgó et al (1998), Fystro (2002 and Russell (2003), for heterogeneous sample sets, showed more accurate prediction of Ct (or Corg) than Nt. Considering literature data as well as results from this study, it was thus difficult to find a clear trend when comparing prediction accuracy for Ct (or Corg) and Nt using sieved samples.…”
Section: Comparison Of Prediction Accuracy For Ct and Ntmentioning
confidence: 81%
See 2 more Smart Citations
“…However, data from Coûteaux et al (2003) for a fairly homogeneous set indicated that prediction accuracy was greater for Ct than for Nt (validation R 2 and CV were 0.99 vs. 0.98 and 6% vs. 10%, respectively). Similarly, data from Salgó et al (1998), Fystro (2002 and Russell (2003), for heterogeneous sample sets, showed more accurate prediction of Ct (or Corg) than Nt. Considering literature data as well as results from this study, it was thus difficult to find a clear trend when comparing prediction accuracy for Ct (or Corg) and Nt using sieved samples.…”
Section: Comparison Of Prediction Accuracy For Ct and Ntmentioning
confidence: 81%
“…Moreover, some other authors have reported that normalisation did not improve the calibration (Shepherd and Walsh, 2002). First derivatives of the spectra have frequently been used for Ct, Corg and Nt prediction (Chang et al, 2001;Reeves et al, 2002;Coûteaux et al, 2003;Russell, 2003;Móron and Cozzolino, 2004) but second derivatives could sometimes result in more accurate results (Salgó et al, 1998;Fystro, 2002). Nevertheless, studying 2 mm sieved topsoil n 1 is the number of samples after the elimination of calibration outliers.…”
Section: Effect Of the Spectrum Preprocessingmentioning
confidence: 99%
See 1 more Smart Citation
“…The first application of NIRS technology for soil analysis was reported in the 1960s (Bowers and Hanks, 1965), with accurate predictions of soil total C and total N contents using NIRS published in the 1970s (AlAbbas et al, 1972), and followed by a greater number of publications in the 1990s (Morra et al, 1991;Sudduth and Hummel, 1993). Numerous papers have addressed soil total C (Dalal and Henry, 1986;Reeves et al, 2002;Russell, 2003;Barthès et al, 2006), organic C (Confalonieri et al, 2001;Shepherd and Walsh, 2002) and inorganic C content (Ben-Dor and Banin, 1990;Salgó et al, 1997;McCarty et al, 2002;Brown et al, 2006) using NIRS in different types of soil and in different environments.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers see in this spectroscopic technique a fast, relatively inexpensive alternative to traditional laboratory methods for the determination of a wide range of soil parameters, like clay, silt, sand, nitrogen, organic matter, moisture, and heavy metal content, to name only a few (e.g., Dalal and Henry, 1986;Ben-Dor and Banin, 1995;Salgó et al, 1998;Hummel et al, 2001;Reeves and McCarty, 2001;Cozzolino and Morón, 2003;Brunet et al, 2007).…”
Section: Introductionmentioning
confidence: 99%